A method for measurement of the vocal tract impedance at the mouth - Kob, Malte; Neuschaefer-Rube, Christiane (Medical engineering & physics, 2002)
In this contribution a method is presented for the measurement of vocal tract resonances. The technique uses a non-invasive acoustic excitation of the vocal tract and a fast and robust detection. The method is an alternative to the linear predictive coding (LPC) analysis for patients with voice and speech disorders. Sweep signals are emitted and recorded simultaneously from the small end of a tube placed in front of the mouth opening. The use of a pressure sensor and a velocity sensor provides a direct measurement of the vocal tract impedance at the mouth (VTMI). For selected sustained German vowels, and some consonants, a comparison of results from LPC analysis and VTMI measurements is given. The results indicate a good agreement in the frequency range from 500 to 5000 Hz. The feasibility of the VTMI method for diagnostic and therapeutic applications is subject to current research.